Childhood physical activity body contact risk: feasibility of a novel technique for objective measurements of impact speed, frequency, and intentionality. (3rd December 2015) - Longmuir, P. E.; Yap, L.‐A.; Bravo, C.; Lee, S. L.; Brandão, L. R.
Abstract : Introduction: Children at risk for bleeding injuries are restricted from body contact during physical activity but current recommendations are based on expert opinion. Aim: Evaluate high‐speed digital video recording as an objective measure of body contact risk during physical activity. Methods: Observational study of physical activities among healthy children, grouped according to participation in teams (vs. individual) and on their perceived risk of injury (high/low). High speed digital video recordings documented the collision target (floor/ground/ice, people, wall, equipment), estimated speed, and impact rates for team and individual activities, with and without expected body contact. Results: Among 348 participating children (3–16 years, 51% female), 32% to 78% experienced at least one contact. Impact type varied significantly (chi‐square, p < 0.001) by activity category. Unstructured and Team high risk activity impacts were primarily with the floor/ground, whereas Individual low risk activities were characterized by equipment impacts. Impact speeds were typically 1.0 to 2.1 m s −1 . Higher impact speeds occurred during instructional classes (2.1 m s −1 ), unstructured free swim (1.9 m s −1 ) and ball hockey (1.7 m s −1 ). Impact rates were higher during Team high risk and Team low risk sports (3.0 and 1.8 impacts per minute, respectively) compared to Individual (high or low risk) or Unstructured activities (0.2–0.3 impacts per minute). Conclusions: High speed video recordings of childhood physical activity are a feasible method for characterizing the frequency, type, direction and speed of impacts. Quantifying the impacts that occur during childhood physical activity could inform the guidelines for physical activity participation among children with identified bleeding risks.